Keyboard material based on silver ion bacteriostasis and preparation method thereof

By using silver ion and comonomer technology in keyboard materials, combined with silver/monmormoryite composite materials, the problem of insufficient antibacterial performance of existing keyboard membranes has been solved, and efficient bacterial inhibition and material performance have been achieved.

CN119899520AInactive Publication Date: 2025-04-29JIANGSU WANXU ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510192987.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing keyboard membranes have limited effectiveness in inhibiting bacterial growth, and some antibacterial technologies may involve heavy metals or harmful chemicals, posing environmental pollution and human health risks.

Method used

Using antibacterial technology based on silver ions, we design comonomers to participate in the synthesis of polyurethane and cooperate with silver/montmorillonite composite materials to control the release rate of silver ions to ensure that it is effective against bacteria and is harmless to the human body.

Benefits of technology

It significantly improves the antibacterial effect of keyboard materials, ensures effective inhibition of bacteria and viruses during use, and does not affect the physical properties and touch of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005280594010000081
    Figure BDA0005280594010000081
Patent Text Reader

Abstract

The invention discloses a keyboard material based on silver ion bacteriostasis and a preparation method thereof, and relates to the technical field of keyboard protective films. Comprising the following steps: step 1, (1) preparing isocyanate-terminated low-molecular polyurethane; (2) preparing to obtain polyurethane resin; step 2, uniformly mixing polyurethane resin, a plasticizer, an anti-aging agent and the silver / montmorillonite composite material, and extruding and granulating in a double-screw extruder to obtain master batches; and melting the master batch, and carrying out film blowing to obtain the keyboard material. The keyboard material has the beneficial effects that by designing the comonomer, the comonomer participates in the synthesis process of polyurethane and cooperates with the silver / montmorillonite composite material, the physical performance and the oxidation resistance of the keyboard material are effectively improved; in addition, based on the action effect of the comonomer and the silver ions, the antibacterial effect of the keyboard material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of keyboard protective films, in particular to a keyboard material based on silver ion antibacterial properties and a preparation method thereof. Background Art

[0002] With the development of electronic technology, keyboards have become an indispensable input device in daily life. However, dust easily accumulates on the surface of keyboards, which becomes a hygienic hazard. Therefore, during use, a layer of keyboard film is usually added to improve the user experience.

[0003] At present, keyboard membrane materials have some defects in antibacterial performance. Although traditional keyboard membranes can provide physical protection against dust and liquid intrusion, they are limited in inhibiting bacterial growth. After long-term use, bacteria and microorganisms accumulated on the surface of the keyboard may cause cross-infection and increase health risks. In addition, the antibacterial technology used in some keyboard membranes may involve heavy metals or harmful chemicals, posing potential environmental pollution and human health risks. Some antibacterial materials may gradually lose their effectiveness due to long-term use, or affect the touch and durability of the keyboard membrane while being antibacterial.

[0004] At the same time, silver ions are widely studied and applied due to their broad-spectrum antibacterial properties. Silver ions can destroy the cell walls of bacteria and the protein shells of viruses, interfere with the DNA replication of microorganisms, and thus effectively inhibit or kill bacteria and viruses. The antibacterial effect of silver ions is long-lasting and not prone to drug resistance, making them ideal antibacterial agents. However, considering the safety and durability of silver ions, it is necessary to control the release rate of silver ions well to ensure that they are harmless to the human body while being effective in antibacterial activities. In summary, in order to solve the above problems, it is of great significance to prepare a keyboard material based on silver ion antibacterial and its preparation method. Summary of the invention

[0005] The object of the present invention is to provide a keyboard material based on silver ion antibacterial and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a keyboard material based on silver ion antibacterial properties, characterized in that it comprises the following steps:

[0008] Step 1: (1) Under a nitrogen atmosphere, diol capsaicin, 1,4-butanediol and toluene diisocyanate are mixed, and stirred at 60-65° C. for 1.5-2.5 hours to obtain isocyanate-terminated low-molecular-weight polyurethane; (2) 1,4-butanediol and tetrafluorobutanediol are mixed; toluene diisocyanate and dibutyltin dilaurate are added; the temperature is raised to 80-85° C. for reaction for 1-2 hours; the temperature is lowered to 40-50° C., isocyanate-terminated low-molecular-weight polyurethane is added, the temperature is raised to 80-85° C. for continuous reaction for 3-4 hours; the temperature is lowered to 50-60° C., 1,4-butanediol and dimethylthiotoluene diamine are added for chain extension for 20-30 minutes, the mixture is cooled to 40° C., neutralized, filtered and washed to obtain a polyurethane resin;

[0009] Step 2: The polyurethane resin, plasticizer, antioxidant and silver / montmorillonite composite material are mixed evenly, and the mixture is placed in a twin-screw extruder for extrusion granulation to obtain a masterbatch; the masterbatch is melted and film-blown to obtain a keyboard material.

[0010] More optimally, the raw materials of the keyboard material include the following components: by weight, 50-55 parts of polyurethane resin, 1-2 parts of plasticizer, 2-3 parts of antioxidant, and 20-22 parts of silver / montmorillonite composite material.

[0011] More optimally, the raw materials of the polyurethane resin include the following components: by weight, 30-34 parts of 1,4-butanediol, 10-16 parts of tetrafluorobutanediol, 25-30 parts of toluene diisocyanate, 0.1-0.2 parts of dibutyltin dilaurate, 8-12 parts of isocyanate-terminated low-molecular polyurethane, 1-1.5 parts of 1,4-butanediol, and 1.5-2 parts of dimethylthiotoluenediamine;

[0012] In the raw materials of the isocyanate-terminated low-molecular-weight polyurethane, the mass ratio of diol capsaicin, 1,4-butanediol and toluene diisocyanate is 32:9:(38-40).

[0013] More optimally, the preparation process of the silver / montmorillonite composite material is as follows: (1) in a nitrogen atmosphere, ultrasonically dispersing montmorillonite in N,N-dimethylformamide, adding isocyanate-terminated low-molecular polyurethane, stirring at 60-65° C. for 5-6 hours, cooling, filtering, and drying to obtain modified montmorillonite; (2) placing the modified montmorillonite in a silver nitrate solution and stirring for 1-2 hours; filtering, transferring to an ascorbic acid solution and stirring for 3-4 hours, filtering, washing, and drying to obtain a silver / montmorillonite composite material.

[0014] More optimally, the raw materials of the modified montmorillonite include montmorillonite and isocyanate-terminated low-molecular polyurethane in a mass ratio of 10:3-5 parts;

[0015] The mass ratio of the modified montmorillonite to the silver nitrate solution is 1:10-12, and the concentration of the silver nitrate solution is 0.8-1.2 mM; the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:10-12, and the concentration of the ascorbic acid solution is 1-1.5 mM.

[0016] More optimally, the preparation method of the diol capsaicin is as follows: (1) methyl catechol, N-(hydroxymethyl) acrylamide, and cation exchange resin are sequentially added to anhydrous ethanol, stirred at 30-40° C. for 5-7 days, filtered, separated, concentrated, washed, and dried to obtain a capsaicin monomer; (2) capsaicin monomer, 3-mercapto-1,2-propanediol, and 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added to methanol and stirred for 10-15 minutes, stirred for 5-10 minutes under ultraviolet light with a wavelength of 356 nm, washed, and dried to obtain a diol capsaicin.

[0017] More optimally, the capsaicin monomer includes the following raw materials by weight: 12-14 parts of methylcatechol, 10-12 parts of N-(hydroxymethyl)acrylamide, 70-80 parts of cation exchange resin, and 500-600 parts of anhydrous ethanol; the diol capsaicin includes the following raw materials by weight: 25 parts of capsaicin monomer, 11-12 parts of 3-mercapto-1,2-propylene glycol, 0.002-0.005 parts of 2,2-dimethoxy-2-phenylethylbenzophenone, and 80-100 parts of methanol.

[0018] Optimally, the temperature of the twin-screw extruder is set as follows: zone 1 165-175°C; zone 2 170-180°C; zone 3 160-170°C; zone 4 170-180°C; the melt temperature is 150-180°C; and the film blowing temperature is 80-100°C.

[0019] More optimally, the plasticizer includes one or more of dioctyl phthalate, di-n-octyl phthalate or dicyclohexyl phthalate; the antioxidant includes one or more of antioxidant 4010NA, antioxidant 264 and antioxidant 4010.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The present invention designs the comonomer to participate in the synthesis process of polyurethane and cooperates with the silver / montmorillonite composite material to effectively improve the physical properties and oxidation resistance of the keyboard material; and based on the effects of the comonomer and silver ions, the antibacterial effect of the keyboard material is further improved. The details are as follows:

[0022] First, in the scheme, diol capsaicin is obtained by organic synthesis and used as a synthetic monomer to participate in the preparation of polyurethane; wherein, diol capsaicin, as a vanillin compound, has strong antibacterial activity; and, the ortho-positioned methoxyl group and hydroxyl group on the benzene ring thereof make it unnecessary to add additional antioxidants in the process of preparing polyurethane, thereby reducing production costs;

[0023] Second, in the scheme, the isocyanate groups contained in the isocyanate-terminated low-molecular-weight polyurethane are combined with the hydroxyl groups on the surface of montmorillonite, thereby coating the surface of montmorillonite to obtain modified montmorillonite; wherein the isocyanate groups contained in the modified montmorillonite and the -NHCOO- groups in the polyurethane segments can both be well combined with silver ions, and then reduced by ascorbic acid to form silver nanoparticles, which are loaded in the modified montmorillonite;

[0024] The low-molecular-weight polyurethane coated on the surface of montmorillonite can interpenetrate with the polyurethane during the preparation of the material, entangle the molecular chains, enhance the thickness of the interface layer and the interface bonding force, improve the compatibility between montmorillonite and the matrix, and also improve the overall mechanical properties;

[0025] The unique layered structure of montmorillonite effectively improves the dispersion of silver nanoparticles, avoids their agglomeration, and enhances the antibacterial effect of the keyboard material; at the same time, its layered structure can not only reflect and absorb electromagnetic waves, reduce the penetration of electromagnetic waves, but also absorb moisture through ion exchange, thereby enhancing the electromagnetic shielding effect and waterproof performance of the keyboard material. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] It should be noted that the following parts are calculated by weight, and the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and are exemplified as follows: in the following embodiments, toluene diisocyanate CAS No. 584-84-9; 1,4-butanediol CAS No. 110-63-4; tetrafluorobutanediol CAS No. 425-61-6; dibutyltin dilaurate CAS No. 77-58-7; methylcatechol CAS No. 452-86-8; N-(hydroxymethyl)acrylamide CAS No. 924-42-5; 3-mercapto-1,2-propylene glycol CAS No. 96-27-5; 2,2-dimethoxy-2-phenylacetophenone CAS No. 24650-42-8.

[0028] The 732 type cationic resin was added to a 5 mol / L hydrochloric acid aqueous solution and soaked for 2 days, washed and dried to obtain a cationic resin for standby use.

[0029] Embodiment 1: A method for preparing a keyboard material based on silver ion antibacterial properties, comprising the following steps:

[0030] Step 1: (1) Under a nitrogen atmosphere, 32 parts of diol capsaicin, 9 parts of 1,4-butanediol, and 38 parts of toluene diisocyanate are mixed, and stirred at 60°C for 1.5 hours to obtain an isocyanate-terminated low-molecular-weight polyurethane; (2) 30 parts of 1,4-butanediol and 10 parts of tetrafluorobutanediol are mixed; 25 parts of toluene diisocyanate and 0.1 parts of dibutyltin dilaurate are added; the temperature is raised to 80°C for reaction for 1 hour; the temperature is lowered to 40°C, 8 parts of isocyanate-terminated low-molecular-weight polyurethane are added, the temperature is raised to 80°C for continuous reaction for 3-4 hours; the temperature is lowered to 50°C, 1 part of 1,4-butanediol and 1.5 parts of dimethylthiotoluene diamine are added for chain extension for 20 minutes, the mixture is cooled to 40°C, neutralized, filtered and washed to obtain a polyurethane resin;

[0031] Step 2: 50 parts of polyurethane resin, 1 part of dioctyl phthalate, 2 parts of antioxidant 264, and 20 parts of silver / montmorillonite composite material are mixed evenly, and placed in a twin-screw extruder for extrusion granulation. The temperature of the twin-screw extruder is set to: 165°C in zone 1; 170°C in zone 2; 160°C in zone 3; 170°C in zone 4 to obtain masterbatch; the masterbatch is melted and film-blown at 80°C to obtain keyboard material;

[0032] The preparation process of diol capsaicin is as follows: (1) 12 parts of methyl catechol, 10 parts of N-(hydroxymethyl) acrylamide, and 70 parts of cation exchange resin are sequentially added to 500 parts of anhydrous ethanol, stirred at 30°C for 5 days, filtered, separated, concentrated, washed, and dried to obtain capsaicin monomer; (2) 25 parts of capsaicin monomer, 11 parts of 3-mercapto-1,2-propylene glycol, and 0.002 parts of 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added to methanol and stirred for 10 minutes, stirred for 5-10 minutes under ultraviolet light with a wavelength of 356 nm, washed, and dried to obtain diol capsaicin;

[0033] The preparation process of the silver / montmorillonite composite material is as follows: (1) under a nitrogen atmosphere, 10 parts of montmorillonite are ultrasonically dispersed in N,N-dimethylformamide, 3 parts of isocyanate-terminated low-molecular polyurethane are added, and the mixture is stirred at 60°C for 5 hours, cooled, filtered, and dried to obtain modified montmorillonite; (2) the modified montmorillonite is placed in a silver nitrate solution and stirred for 1 hour (the mass ratio of the modified montmorillonite to the silver nitrate solution is 1:10, and the concentration of the silver nitrate solution is 0.8 mM); filtered, transferred to an ascorbic acid solution and stirred for 3 hours (the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:10, and the concentration of the ascorbic acid solution is 1 mM), filtered, washed, and dried to obtain a silver / montmorillonite composite material.

[0034] Embodiment 2: A method for preparing a keyboard material based on silver ion antibacterial properties, comprising the following steps:

[0035] Step 1: (1) Under a nitrogen atmosphere, 32 parts of diol capsaicin, 9 parts of 1,4-butanediol, and 40 parts of toluene diisocyanate are mixed, and stirred at 65°C for 2.5 hours to obtain an isocyanate-terminated low-molecular-weight polyurethane; (2) 34 parts of 1,4-butanediol and 16 parts of tetrafluorobutanediol are mixed; 30 parts of toluene diisocyanate and 0.2 parts of dibutyltin dilaurate are added; the temperature is raised to 85°C for reaction for 2 hours; the temperature is lowered to 50°C, 12 parts of isocyanate-terminated low-molecular-weight polyurethane are added, the temperature is raised to 85°C for further reaction for 4 hours; the temperature is lowered to 60°C, 1.5 parts of 1,4-butanediol and 2 parts of dimethylthiotoluene diamine are added for chain extension for 30 minutes, the mixture is cooled to 40°C, neutralized, filtered and washed to obtain a polyurethane resin;

[0036] Step 2: 55 parts of polyurethane resin, 2 parts of dioctyl phthalate, 3 parts of antioxidant 264, and 22 parts of silver / montmorillonite composite material are mixed evenly, and placed in a twin-screw extruder for extrusion granulation. The temperature of the twin-screw extruder is set to: 175°C in zone 1; 180°C in zone 2; 170°C in zone 3; 180°C in zone 4 to obtain masterbatch; the masterbatch is melted and film-blown at 100°C to obtain keyboard material;

[0037] The preparation process of diol capsaicin is as follows: (1) 14 parts of methyl catechol, 12 parts of N-(hydroxymethyl) acrylamide, and 80 parts of cation exchange resin are sequentially added to 600 parts of anhydrous ethanol, stirred at 40°C for 7 days, filtered, separated, concentrated, washed, and dried to obtain capsaicin monomer; (2) 25 parts of capsaicin monomer, 12 parts of 3-mercapto-1,2-propylene glycol, and 0.005 parts of 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added to methanol and stirred for 15 minutes, stirred for 10 minutes under ultraviolet light with a wavelength of 356 nm, washed, and dried to obtain diol capsaicin;

[0038] The preparation process of the silver / montmorillonite composite material is as follows: (1) under a nitrogen atmosphere, 10 parts of montmorillonite are ultrasonically dispersed in N,N-dimethylformamide, 3 parts of isocyanate-terminated low-molecular polyurethane are added, and the mixture is stirred at 65°C for 6 hours, cooled, filtered, and dried to obtain modified montmorillonite; (2) the modified montmorillonite is placed in a silver nitrate solution and stirred for 2 hours (the mass ratio of the modified montmorillonite to the silver nitrate solution is 1:12, and the concentration of the silver nitrate solution is 1.2 mM); filtered, transferred to an ascorbic acid solution and stirred for 4 hours (the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:12, and the concentration of the ascorbic acid solution is 1.5 mM), filtered, washed, and dried to obtain a silver / montmorillonite composite material.

[0039] Embodiment 3: A method for preparing a keyboard material based on silver ion antibacterial properties, comprising the following steps:

[0040] Step 1: (1) Under a nitrogen atmosphere, 32 parts of diol capsaicin, 9 parts of 1,4-butanediol, and 40 parts of toluene diisocyanate are mixed, and stirred at 62° C. for 2 hours to obtain an isocyanate-terminated low-molecular-weight polyurethane; (2) 32 parts of 1,4-butanediol and 15 parts of tetrafluorobutanediol are mixed; 26 parts of toluene diisocyanate and 0.2 parts of dibutyltin dilaurate are added; the temperature is raised to 82° C. for reaction for 1.5 hours; the temperature is lowered to 45° C., 10 parts of isocyanate-terminated low-molecular-weight polyurethane are added, the temperature is raised to 82° C. for continuous reaction for 3.5 hours; the temperature is lowered to 55° C., 1.2 parts of 1,4-butanediol and 1.8 parts of dimethylthiotoluene diamine are added for chain extension for 25 minutes, the mixture is cooled to 40° C., neutralized, filtered and washed to obtain a polyurethane resin;

[0041] Step 2: 52 parts of polyurethane resin, 1.5 parts of dioctyl phthalate, 2.5 parts of antioxidant 264, and 21 parts of silver / montmorillonite composite material are mixed evenly, and placed in a twin-screw extruder for extrusion granulation. The temperature of the twin-screw extruder is set to: 170°C in zone 1; 175°C in zone 2; 165°C in zone 3; 175°C in zone 4 to obtain masterbatch; the masterbatch is melted and film-blown at 90°C to obtain keyboard material;

[0042] The preparation process of diol capsaicin is as follows: (1) 13 parts of methyl catechol, 11 parts of N-(hydroxymethyl) acrylamide, and 75 parts of cation exchange resin are sequentially added to 550 parts of anhydrous ethanol, stirred at 35° C. for 6 days, filtered, separated, concentrated, washed, and dried to obtain capsaicin monomer; (2) 25 parts of capsaicin monomer, 11.5 parts of 3-mercapto-1,2-propylene glycol, and 0.005 parts of 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added to methanol and stirred for 15 minutes, stirred for 10 minutes under ultraviolet light with a wavelength of 356 nm, washed, and dried to obtain diol capsaicin;

[0043] The preparation process of the silver / montmorillonite composite material is as follows: (1) under a nitrogen atmosphere, 10 parts of montmorillonite are ultrasonically dispersed in N,N-dimethylformamide, 3 parts of isocyanate-terminated low-molecular polyurethane are added, and the mixture is stirred at 62° C. for 5.5 hours, cooled, filtered, and dried to obtain a modified montmorillonite; (2) the modified montmorillonite is placed in a silver nitrate solution and stirred for 1.5 hours (the mass ratio of the modified montmorillonite to the silver nitrate solution is 1:11, and the concentration of the silver nitrate solution is 1 mM); filtered, transferred to an ascorbic acid solution and stirred for 3.5 hours (the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:11, and the concentration of the ascorbic acid solution is 1.5 mM), filtered, washed, and dried to obtain a silver / montmorillonite composite material.

[0044] Comparative Example 1: Silver-loaded calcium phosphate was used instead of the silver / montmorillonite composite material, and the rest was the same as in Example 3.

[0045] Comparative Example 2: No diol capsaicin was added as a comonomer, and the rest was the same as Example 3, specifically as follows:

[0046] Step 1: (1) Under a nitrogen atmosphere, 9 parts of 1,4-butanediol and 40 parts of toluene diisocyanate are mixed, and stirred at 62° C. for 2 hours to obtain an isocyanate-terminated low-molecular-weight polyurethane; (2) 32 parts of 1,4-butanediol and 15 parts of tetrafluorobutanediol are mixed; 26 parts of toluene diisocyanate and 0.2 parts of dibutyltin dilaurate are added; the temperature is raised to 82° C. for reaction for 1.5 hours; the temperature is lowered to 45° C., 10 parts of isocyanate-terminated low-molecular-weight polyurethane are added, the temperature is raised to 82° C. for further reaction for 3.5 hours; the temperature is lowered to 55° C., 1.2 parts of 1,4-butanediol and 1.8 parts of dimethylthiotoluene diamine are added for chain extension for 25 minutes, the mixture is cooled to 40° C., neutralized, filtered and washed to obtain a polyurethane resin;

[0047] Step 2: 52 parts of polyurethane resin, 1.5 parts of dioctyl phthalate, 2.5 parts of antioxidant 264, and 21 parts of silver / montmorillonite composite material are mixed evenly, and placed in a twin-screw extruder for extrusion granulation. The temperature of the twin-screw extruder is set to: 170°C in zone 1; 175°C in zone 2; 165°C in zone 3; 175°C in zone 4 to obtain masterbatch; the masterbatch is melted and film-blown at 90°C to obtain keyboard material;

[0048] The preparation process of the silver / montmorillonite composite material is as follows: (1) under a nitrogen atmosphere, 10 parts of montmorillonite are ultrasonically dispersed in N,N-dimethylformamide, 3 parts of isocyanate-terminated low-molecular polyurethane are added, and the mixture is stirred at 62° C. for 5.5 hours, cooled, filtered, and dried to obtain a modified montmorillonite; (2) the modified montmorillonite is placed in a silver nitrate solution and stirred for 1.5 hours (the mass ratio of the modified montmorillonite to the silver nitrate solution is 1:11, and the concentration of the silver nitrate solution is 1 mM); filtered, transferred to an ascorbic acid solution and stirred for 3.5 hours (the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:11, and the concentration of the ascorbic acid solution is 1.5 mM), filtered, washed, and dried to obtain a silver / montmorillonite composite material.

[0049] Comparative Example 3: No silver / montmorillonite composite material was added, and the rest was the same as Example 3.

[0050] Comparative Example 4: The concentration of the silver nitrate solution was increased, and the rest was the same as in Example 3, as follows:

[0051] Step 1: (1) Under a nitrogen atmosphere, 32 parts of diol capsaicin, 9 parts of 1,4-butanediol, and 40 parts of toluene diisocyanate are mixed, and stirred at 62° C. for 2 hours to obtain an isocyanate-terminated low-molecular-weight polyurethane; (2) 32 parts of 1,4-butanediol and 15 parts of tetrafluorobutanediol are mixed; 26 parts of toluene diisocyanate and 0.2 parts of dibutyltin dilaurate are added; the temperature is raised to 82° C. for reaction for 1.5 hours; the temperature is lowered to 45° C., 10 parts of isocyanate-terminated low-molecular-weight polyurethane are added, the temperature is raised to 82° C. for continuous reaction for 3.5 hours; the temperature is lowered to 55° C., 1.2 parts of 1,4-butanediol and 1.8 parts of dimethylthiotoluene diamine are added for chain extension for 25 minutes, the mixture is cooled to 40° C., neutralized, filtered and washed to obtain a polyurethane resin;

[0052] Step 2: 52 parts of polyurethane resin, 1.5 parts of dioctyl phthalate, 2.5 parts of antioxidant 264, and 21 parts of silver / montmorillonite composite material are mixed evenly, and placed in a twin-screw extruder for extrusion granulation. The temperature of the twin-screw extruder is set to: 170°C in zone 1; 175°C in zone 2; 165°C in zone 3; 175°C in zone 4 to obtain masterbatch; the masterbatch is melted and film-blown at 90°C to obtain keyboard material;

[0053] The preparation process of diol capsaicin is as follows: (1) 13 parts of methyl catechol, 11 parts of N-(hydroxymethyl) acrylamide, and 75 parts of cation exchange resin are sequentially added to 550 parts of anhydrous ethanol, stirred at 35° C. for 6 days, filtered, separated, concentrated, washed, and dried to obtain capsaicin monomer; (2) 25 parts of capsaicin monomer, 11.5 parts of 3-mercapto-1,2-propylene glycol, and 0.005 parts of 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added to methanol and stirred for 15 minutes, stirred for 10 minutes under ultraviolet light with a wavelength of 356 nm, washed, and dried to obtain diol capsaicin;

[0054] The preparation process of the silver / montmorillonite composite material is as follows: (1) under a nitrogen atmosphere, 10 parts of montmorillonite are ultrasonically dispersed in N,N-dimethylformamide, 3 parts of isocyanate-terminated low-molecular polyurethane are added, and the mixture is stirred at 62° C. for 5.5 hours, cooled, filtered, and dried to obtain a modified montmorillonite; (2) the modified montmorillonite is placed in a silver nitrate solution and stirred for 1.5 hours (the mass ratio of the modified montmorillonite to the silver nitrate solution is 1:11, and the concentration of the silver nitrate solution is 10 mM); filtered, transferred to an ascorbic acid solution and stirred for 3.5 hours (the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:11, and the concentration of the ascorbic acid solution is 1.5 mM), filtered, washed, and dried to obtain a silver / montmorillonite composite material.

[0055] Performance test 1: The keyboard materials obtained in the embodiment and the comparative example were subjected to performance testing, wherein the tensile strength was measured using a universal tensile testing machine; and, in accordance with GB / T9349-2002B, the keyboard materials were placed with a spacing of more than 2 cm and a spacing of more than 7 cm from the box wall, with a wind speed of 0.5-1.0 m / s, ventilation of 10-100 times / h, a temperature of 100°C, and oven heat aging for 48 hours, and the tensile strength was measured;

[0056] The antibacterial property was measured according to QB / T2591 method, and the detected bacteria were Escherichia coli and Staphylococcus aureus; the obtained data are shown in the following table.

[0057]

[0058] Table 1

[0059] Conclusion: From the data in the above table, it can be seen that the embodiment effectively improves the physical properties and antioxidant properties of the keyboard material by designing the comonomer to participate in the synthesis process of polyurethane and cooperate with the silver / montmorillonite composite material; and based on the effect of the comonomer and silver ions, the antibacterial effect of the keyboard material is further improved. Therefore, during the thermal aging process, the retention rate of the tensile strength of the embodiment is above 90%. Comparative Example 1 uses silver-loaded calcium phosphate. Compared with the silver / montmorillonite composite material, its silver ion dispersion is not good, and it is difficult to control the release rate of silver ions, which increases the difficulty of preparation; Comparative Example 2 does not add diol capsaicin as a comonomer, and the antibacterial and antioxidant properties are reduced; Comparative Example 3 does not add silver / montmorillonite composite materials, and the physical properties and antibacterial properties are reduced; Comparative Example 4 increases the concentration of silver nitrate solution, and the antibacterial properties of the material are reduced, because, at higher concentrations, silver particles will aggregate and settle, even if montmorillonite can act as a carrier, it will be unevenly distributed, and the performance will be reduced.

[0060] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a keyboard material based on silver ion antibacterial properties, characterized in that: The following steps are involved: Step 1: (1) Under a nitrogen atmosphere, diol capsaicin, 1,4-butanediol and toluene diisocyanate are mixed, and stirred at 60-65° C. for 1.5-2.5 hours to obtain isocyanate-terminated low-molecular-weight polyurethane; (2) 1,4-butanediol and tetrafluorobutanediol are mixed; toluene diisocyanate and dibutyltin dilaurate are added; the temperature is raised to 80-85° C. for reaction for 1-2 hours; the temperature is lowered to 40-50° C., isocyanate-terminated low-molecular-weight polyurethane is added, the temperature is raised to 80-85° C. for continuous reaction for 3-4 hours; the temperature is lowered to 50-60° C., 1,4-butanediol and dimethylthiotoluene diamine are added for chain extension for 20-30 minutes, the mixture is cooled to 40° C., neutralized, filtered and washed to obtain a polyurethane resin; Step 2: The polyurethane resin, plasticizer, antioxidant and silver / montmorillonite composite material are mixed evenly, and the mixture is placed in a twin-screw extruder for extrusion granulation to obtain a masterbatch; the masterbatch is melted and film-blown to obtain a keyboard material.

2. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The raw materials of the keyboard material include the following components: by weight, 50-55 parts of polyurethane resin, 1-2 parts of plasticizer, 2-3 parts of antioxidant, and 20-22 parts of silver / montmorillonite composite material.

3. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The raw materials of the polyurethane resin include the following components: by weight, 30-34 parts of 1,4-butanediol, 10-16 parts of tetrafluorobutanediol, 25-30 parts of toluene diisocyanate, 0.1-0.2 parts of dibutyltin dilaurate, 8-12 parts of isocyanate-terminated low-molecular polyurethane, 1-1.5 parts of 1,4-butanediol, and 1.5-2 parts of dimethylthiotoluenediamine; In the raw materials of the isocyanate-terminated low-molecular-weight polyurethane, the mass ratio of diol capsaicin, 1,4-butanediol and toluene diisocyanate is 32:9:(38-40).

4. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The preparation process of the silver / montmorillonite composite material is as follows: (1) in a nitrogen atmosphere, ultrasonically dispersing montmorillonite in N,N-dimethylformamide, adding isocyanate-terminated low-molecular-weight polyurethane, stirring at 60-65° C. for 5-6 hours, cooling, filtering, and drying to obtain modified montmorillonite; (2) placing the modified montmorillonite in a silver nitrate solution and stirring for 1-2 hours; The mixture was filtered, transferred to an ascorbic acid solution and stirred for 3-4 hours, filtered, washed and dried to obtain a silver / montmorillonite composite material.

5. The method for preparing a keyboard material based on silver ion antibacterial according to claim 4, characterized in that: The raw materials of the modified montmorillonite include montmorillonite and isocyanate-terminated low-molecular polyurethane in a mass ratio of 10:3-5 parts; The mass ratio of the modified montmorillonite to the silver nitrate solution is 1:10-12, and the concentration of the silver nitrate solution is 0.8-1.2 mM; the mass ratio of the modified montmorillonite to the ascorbic acid solution is 1:10-12, and the concentration of the ascorbic acid solution is 1-1.5 mM.

6. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The preparation method of the diol capsaicin is as follows: (1) methyl catechol, N-(hydroxymethyl) acrylamide and cation exchange resin are sequentially added into anhydrous ethanol, stirred at 30-40° C. for 5-7 days, filtered, separated, concentrated, washed and dried to obtain a capsaicin monomer; (2) capsaicin monomer, 3-mercapto-1,2-propylene glycol and 2,2-dimethoxy-2-phenylethylbenzophenone are sequentially added into methanol and stirred for 10-15 minutes, stirred for 5-10 minutes under ultraviolet light with a wavelength of 356 nm, washed and dried to obtain the diol capsaicin.

7. The method for preparing a keyboard material based on silver ion antibacterial according to claim 6, characterized in that: The capsaicin monomer includes the following raw materials by weight: 12-14 parts of methyl catechol, 10-12 parts of N-(hydroxymethyl) acrylamide, 70-80 parts of cation exchange resin, and 500-600 parts of anhydrous ethanol; the diol capsaicin includes the following raw materials by weight: 25 parts of capsaicin monomer, 11-12 parts of 3-mercapto-1,2-propylene glycol, 0.002-0.005 parts of 2,2-dimethoxy-2-phenylethylbenzophenone, and 80-100 parts of methanol.

8. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The temperature of the twin-screw extruder is set to: zone 1 165-175°C; zone 2 170-180°C; zone 3 160-170°C; zone 4 170-180°C; the melting temperature is 150-180°C; and the film blowing temperature is 80-100°C.

9. The method for preparing a keyboard material based on silver ion antibacterial according to claim 1, characterized in that: The plasticizer includes one or more of dioctyl phthalate, di-n-octyl phthalate or dicyclohexyl phthalate; the antioxidant includes one or more of antioxidant 4010NA, antioxidant 264 and antioxidant 4010.

10. A keyboard material prepared according to the method for preparing a keyboard material based on silver ion antibacterial properties according to any one of claims 1 to 9.